2012
DOI: 10.1016/j.breast.2011.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Predictive value of peripheral blood lymphocyte count in breast cancer patients treated with primary chemotherapy

Abstract: Peripheral blood lymphocyte (PBL) count may reflect the immune status of cancer patients. We retrospectively analyzed the predictive and prognostic impact of baseline and post-chemotherapy PBL counts in a homogeneous group of 103 breast cancer patients treated with neoadjuvant chemotherapy (anthracyclines and taxanes). In univariate analysis, baseline PBL under 1500 × 10(6)/L (p = 0.013; hazard ratio [HR]: 2.80, 95%CI 1.24-6.61), and PBL decrease >200 × 10(6)/L after the first cycle of chemotherapy (p = 0.047;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
40
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(42 citation statements)
references
References 40 publications
2
40
0
Order By: Relevance
“…It has also been reported that low cholesterol level is correlated with poor prognosis in various malignancies as the cholesterol may affect the caloric intake and cell membrane formation 40,41 . What is more, low peripheral lymphocyte count is an indicator for the inadequate host immune response and is correlated to undesirable prognosis in various cancers, including breast cancer 9,42,43 . Thus, the combination of these three parameters could integrate the accuracy of each parameter to assess for the general condition.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been reported that low cholesterol level is correlated with poor prognosis in various malignancies as the cholesterol may affect the caloric intake and cell membrane formation 40,41 . What is more, low peripheral lymphocyte count is an indicator for the inadequate host immune response and is correlated to undesirable prognosis in various cancers, including breast cancer 9,42,43 . Thus, the combination of these three parameters could integrate the accuracy of each parameter to assess for the general condition.…”
Section: Discussionmentioning
confidence: 99%
“…It is well established that breast cancer cell metastasis to the axillary lymph node is associated with increased mortality [1, 2]. Notably, the immune status of patients can influence its clinical course [3]. For instance, decreased infiltration of CD8 + cytotoxic T-lymphocytes (CTLs) in tumor has been associated with lymph node metastasis and poor response to neoadjuvant chemotherapy [46], while the activation of immune responses has been related to improved overall survival in patients with breast cancer [7].…”
Section: Introductionmentioning
confidence: 99%
“…Various reports found a relationship between ALC, NLR and PLR and prognosis of breast cancer, most of the studies focusing on LRBP of baseline. [6][7][8][9][10] However, only a few studies focused on the impact of radiotherapy on LRBP in relation to prognosis. And in these research, time points of LRBP were artificial selection, and most of them were before or after radiotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5] Lymphocyte-related blood parameters (LRBP), including absolute lymphocyte counts (ALC), neutrophil-to-lymphocyte ratio (NLR), and platelet-to-lymphocyte ratio (PLR), representatives of inflammatory factors, can reflect the immune system status. [6][7][8] Various reports found a relationship between ALC, NLR, and PLR and prognosis of breast cancer. [6][7][8][9][10] Most of the studies focused on baseline LRBP.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation